Essential Tremor as a “Waste Basket” Diagnosis: Diagnosing Essential Tremor Remains a Challenge - Amlang, Christian J.; Trujillo Diaz, Daniel; Louis, Elan D. (Frontiers in Neurology, 2020)
Introduction: The diagnosis of essential tremor (ET) remains a clinical one and diagnostic errors are common. We aimed to (1) determine precisely how frequently ET diagnoses are misapplied (i.e., what percentage of patients who have been assigned an “ET” diagnosis actually have another movement disorder), (2) determine which other movement disorders are most often misclassified as “ET”, and (3) examine the clinical features that were most associated with diagnostic errors. Methods: Eighty-four consecutive patients were included who met the following criteria: (1) initial outpatient evaluation by one of the authors (E.D.L.) between January 2015 and July 2019 and (2) pre-evaluation diagnosis of ET. Data on an extensive number of clinical features were extracted from the electronic medical record. Results: Forty (47.6%) patients received a post-evaluation diagnosis of ET, 22 (26.2%) of dystonia and 22 (26.2%) of other diagnoses including Parkinson’s disease (PD) (5 [6.0%]). Factors associated with an alternative post-evaluation diagnosis other than ET were: pre-evaluation diagnosis made by a non-neurologist, shorter tremor duration, irregular tremor, abnormal limb postures, among others. Discussion: Diagnosing ET remains a challenge, with the diagnosis being over-applied and being used as a “waste basket”. More than one-half of the patients who were referred to our clinic with an intake diagnosis of ET were given an alternative post-evaluation diagnosis. While PD was reported to be the most frequently missed diagnosis in past study, dystonia was most commonly missed in our study. Several clinical features can help to differentiate ET from other tremor disorders.